Socialization of Digital Marketing and Fintech Literacy for Micro & Small Businesses in Samarinda City - Adhimursandi, Doddy; Azis, Musdalifah; Heksarini, Ariesta; Asnawati, Asnawati (PT. Riset Press International, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a vital component of the community economy, and their success is crucial for economic growth. Despite the increasing digitalization of the world, many MSMEs continue to rely on traditional business methods, such as using printed money. This presents a challenge for MSMEs to keep pace with changing times and compete in the digital era. To overcome this obstacle, it is imperative to provide education and direct assistance to MSME partners on how to apply digital marketing and financial technology. This can be accomplished through socialization programs that educate partners about digital marketing and fintech, as well as provide them with the necessary steps to register in the Gojek application as a marketplace tool. The mentoring stage is also critical for ensuring that partners can apply the provided technology and utilize online platforms to facilitate sales. By providing partners with the necessary skills and knowledge, MSMEs can increase their sales efficiency and contribute to economic growth. In summary, the support and assistance provided to MSMEs in adopting digital marketing and financial technology are necessary to ensure their survival and success in the digital era. MSMEs can increase their sales efficiency and contribute to economic growth through the right education and mentoring.